Effects of pregnancy on breast cancer immunology: immune biomarker and TIL quantification - Galas, Kristin; Gleitsmann, Moritz; Rey, Julia; Solbach, Christine; Witzel, Isabell; Karn, Thomas; Schmatloch, Sabine; Schem, Christian; Schneeweiss, Andreas; Sinn, Bruno; Fehm, Tanja; Denkert, Carsten; et al. (npj Breast cancer, 2025)
Breast cancer diagnosed during pregnancy (PrBC) is a rare occurrence but may become more prevalent as women nowadays tend to postpone childbearing until later in life. Further understanding of how pregnancy affects the tumor microenvironment (TME) is essential. We constructed Tissue Microarrays (TMA) of tumor specimens from 126 pregnant breast cancer (BC) patients and examined standard BC markers such as ER, PR, Ki67, HER2, tumor infiltrating lymphocytes (TILs), and immunomarkers HLA class I, HLA-G, PD-L1, TIGIT and Nectin-4. Subsequently, we compared our findings with those from a matched non-pregnant cohort of young BC patients. Pregnant BC patients were younger, had significantly higher proliferation rates and a higher expression of Nectin-4. Higher pregnancy related estrogen levels may boost proliferation und Nectin-4 overexpression, promoting BC progression. No further evidence supporting impaired maternal anti-tumor response in BC was observed in this study.